Level of Education and Perceptions of the Quality of Services to Prevent Radicalism: A Study in Poso District, Indonesia - Karsono, Bambang (International Journal of Scientific Research and Management (IJSRM), 2022)
This study analyzes the differences in public perceptions of the quality of radicalism prevention services from the point of view of the level of education. Education has been used to radicalize and deradicalize youth. Governments in conflict-affected countries have an interest in funding measures against violent extremism as part of education programs. After the social conflict in the Poso district, the local government implemented some policies aimed at preventing the emergence of radicalism. The results of the study of 456 respondents from four elements of the population, namely the army, police, government employees, and the general public, showed that the level of education was the difference between people’s perceptions of the quality of radicalism prevention services. Respondents with high school education were able to have a higher average response than those with a college education.